(untitled) (Journal of the Management Sciences, 2026)
Digital entrepreneurship has become a pivotal element in the global economy, transforming conventional business models and generating fresh avenues for innovation and expansion. Within the modern business environment, digital entrepreneurship stands out as a powerful catalyst, redefining traditional entrepreneurial frameworks and the skill sets necessary for achieving success. The study focuses on the effect of digital entrepreneurship on students entrepreneurial capabilities in Dennis Osadebay University, Asaba. The study adopted a cross sectional survey research design and the sample size of 185 respondents was selected from the population of 344 students in faculty of management sciences, Dennis Osadebay University. Data collected was analyzed using multiple regression. Findings revealed that digital innovation has significant influence on entrepreneurial driven capabilities. E-commerce has significant influence on entrepreneurial driven capabilities. Data analytics has significant effect on entrepreneurial driven capabilities. The study comes to the conclusion that students possess both the enthusiasm and foundational skills needed to succeed in the digital innovation and entrepreneurial space. However, the full potential of these capabilities is not being maximized due to a lack of institutional frameworks, mentorship opportunities, and real-world practice. The study recommended that real-world entrepreneurial and digital experience through internships or startup collaborations should be encouraged to bridge the gap between classroom learning and business practice.